PENGARUH PENGGUNAAN METODE SHOW AND TELL TERHADAP KEMAMPUAN BERCERITA SISWA KELAS IV SD INPRES 6/86 BALLE KECAMATAN KAHU KABUPATEN BONE - Rukayah; Abd. Kadir; Andi Rizky Aulia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Abstract: This research aims to determine the effect of using the Show and Tell method on the storytelling ability of fourth-grade students at SD Inpres 6/86 Balle, Kahu District, Bone Regency, using a quantitative method. The research design used is the One Group Pretest-Posttest Design. The variables in this study are the Show and Tell method and storytelling ability. The population in this study consists of all fourth-grade students at SD Inpres 6/86 Balle, with a sample of 29 students selected using saturated sampling technique. The data collection technique used was a test to determine the students' storytelling ability before and after using the Show and Tell method. The data analysis used descriptive statistical analysis and inferential statistical analysis. The results of this study indicate that before using the Show and Tell method, the pretest scores obtained by the students tended to be less capable with an average (Mean) of 33.97, and after using the Show and Tell method, the posttest scores of the students increased with an average of 66.38 and fell into the fairly capable category. The conclusion of this research is that there is a significant influence on the storytelling ability of students before and after using the Show and Tell method among the fourth-grade students of SD Inpres 6/86 Balle, Kahu District, Bone Regency.